Solved the enigma of pediatric severe acute hepatitis of unknown origin? - Rodriguez-Frias, Francisco; Rando-Segura, Ariadna; Quer, Josep (Frontiers in Cellular and Infection Microbiology, 2023)
Hepatitis is an inflammation of the liver whose etiology is very heterogeneous. The most common cause of hepatitis is viral infections from hepatotropic viruses, including hepatitis A, B, C, D and E. However, other factors such as infections from other agents, metabolic disorders, or autoimmune reactions can also contribute to hepatitis, albeit to a lesser extent. On April 5, 2022, the United Kingdom Health Security Agency (UKHSA, 2022) alerted the World Health Organization (WHO) on the increased incidence of severe acute hepatitis of unknown causes (not A-E) in previously healthy young children, with symptoms of liver failure that in some cases required liver transplantation. By July 2022, 1,296 cases were reported in 37 countries (Table 1). Acute hepatitis of unknown causes is not an exceptional phenomenon: in fact, it represents more than 30% of cases of acute hepatitis in children, however in the present instance the large proportion of severe cases was surprising and alarming (6% of liver transplants and almost 3% mortality). Multiple hypotheses have been proposed to explain the etiology of such higher proportion of acute hepatitis, including their co-occurrence in the context of COVID-19 pandemic. This is a review of the history of a clinical threat that has put in check a world health care system highly sensitized by the current COVID-19 pandemics, and that it looks like has ended with the arguments that the severe acute pediatric hepatitis is caused by Adeno-associated virus 2 (AAV2) infection associated with a coinfection with a helper virus (human Adenovirus HAdV or human herpesvirus 6 (HHV6) in susceptible children carrying HLA-class II antigen HLA-DRB1*04:01.